The Ambivalent U.S. Context of Reception and the Dichotomous Legal Consciousness of Unaccompanied Minors. (29th October 2019) - Galli, Chiara
Abstract: This article examines the effects of contradictory U.S. immigration laws on unaccompanied minors from Central America. As children, they are considered deserving of protection, but as undocumented immigrants, they are subjected to state legal violence. Apprehended at the border, they must interact with multiple immigration agencies and finally apply for humanitarian deportation relief. Interactions in these institutional spaces teach youths about U.S. laws and behavioral norms expected of young claimants deemed deserving of humanitarian protection, which are construed in contrast to discourses that stigmatize their co-ethnics as "bad" immigrants. These interactions shape youths' sense of belonging and commonsense understanding of the law or legal consciousness. I argue that the "legal consciousness" of unaccompanied minors is dichotomous and characterized by: (1) a combination of trust and fear in the state; (2) concurrent feelings of deservingness/rights and stigma/subordination; (3) information and misinformation about U.S. laws. This dichotomous consciousness shapes how youths claim belonging and rights in social interactions and in their applications for legal status. To signal their own belonging and deservingness, youths leverage information about their rights and normative notions about desirable teen and migrant behavior. Yet, in the process, they also inadvertently perpetuate stigmas about co-ethnics.